2017
DOI: 10.1155/2017/3954181
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula angustifolia Mill. Oil and Its Active Constituent Linalyl Acetate Alleviate Pain and Urinary Residual Sense after Colorectal Cancer Surgery: A Randomised Controlled Trial

Abstract: Pain and urinary symptoms following colorectal cancer (CRC) surgery are frequent and carry a poor recovery. This study tested the effects of inhalation of Lavandula angustifolia Mill. (lavender) oil or linalyl acetate on pain relief and lower urinary tract symptoms (LUTS) following the removal of indwelling urinary catheters from patients after CRC surgery. This randomised control study recruited 66 subjects with indwelling urinary catheters after undergoing CRC surgery who later underwent catheter removal. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Furthermore, the essential oil obtained from lavender is an interesting object for trials considering biological activity and even in medicinal trials. Some studies and overviews from recent years mention the anti-aging, analgesic, nuroprotective, sedative or anticancer activities of lavender essential oil [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. These various lavender essential oil applications are due to their unique chemical composition, rich in monoterpenes, sesquiterpenes, sesquiterpenoids, aliphatic compounds and especially an abundance of monoterpenoids [ 10 ], with linalool and linalyl acetate highlighted as main flower components [ 1 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the essential oil obtained from lavender is an interesting object for trials considering biological activity and even in medicinal trials. Some studies and overviews from recent years mention the anti-aging, analgesic, nuroprotective, sedative or anticancer activities of lavender essential oil [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. These various lavender essential oil applications are due to their unique chemical composition, rich in monoterpenes, sesquiterpenes, sesquiterpenoids, aliphatic compounds and especially an abundance of monoterpenoids [ 10 ], with linalool and linalyl acetate highlighted as main flower components [ 1 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ability of linalyl acetate to preserve total weight and IGF-1 levels suggests that linalyl acetate maintains overall physique, and that its ability to prevent muscle atrophy could be indirectly estimated. Lavender treatment tended to preserve muscle mass and ber size even without signi cantly increasing IGF-1 levels, suggesting that the analgesic effect of lavender contributed to its maintenance of mobility [21,37]. The loss of muscle mass and function in our rat model of RA and HTN suggests that current pharmaceutical interventions have severe limitations due to their inability to reverse muscle weakness, because increased muscle mass does not guarantee improved muscle function [38].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, lavender oil has possibility of preventing cardiovascular disease based on anti-diabetic [14] and antithrombotic activities [15]. Linalyl acetate, a volatile and low toxicity compound contained in citrus fruits, is the main component of lavender oil [16] Linalyl acetate has shown anti-in ammatory effects in vitro [17] and in vivo [18], as well as anti-hypertensive [19], anti-diabetic [20] and anti-stress [21] effects with the ability to prevent vascular endothelium dysfunction [18]. These pharmacological properties suggested that lavender and linalyl acetate could have preventive effects in our rat model of RA with chronic nicotine-induced HTN.…”
Section: Introductionmentioning
confidence: 99%
“…Sedative effect of lavender during neurasthenia and heightened pulse is achieved through baths. It is also used in dental practice for inhalation treatment of rhinites, laryngitis; it is applied to speed up the wound healing after surgeries (Wang et al, 2012;Yu & Seol, 2017;Mekonnen et al, 2019). Lavender oil is used to improve the odor of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively thorough degree of study of the chemical composition and application of those plants during separate human and animal diseases (Wynn & Fougère, 2007;Lee et al, 2014;Zarei et al, 2014;Kubo et al, 2015;Saberi et al, 2016;Dolatabadi et al, 2018;EFSA Panel et al, 2020;Torki et al, 2021), no complex impact of these three species of medicinal plants during high-fat diet and excessive consumption of food was found. Therefore, the objectives of this study were overall effects of M. officinalis, L. angusti folia, V. agnus-castus on weight gain, changes in index of body weight, biochemical and morphological blood parameters, orienting-motor activity and emotional status of white laboratory rats against the background of excessive fat diet.…”
Section: Introductionmentioning
confidence: 99%